ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFFECTIVE TAX RATE PADA PERUSAHAAN REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA - Desy Yanuari Simarmata, 11.05.52.0105; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2015)
This study aimed to analyze the effect of firm size, leverage, inventory intensity, profitability, fixed asset intensity, and independent commissioner to effective tax rate (ETR). The object of this study is on the Real Estate and Property Company listed on the Indonesia Stock Exchange (IDX) 2010-2013. The sampling method used is purposive sampling. The data analysis technique used is multiple linear regression. The results of this study indicate that the coefficient of determination values obtained Adjusted R Square of 0.359, this means the ability of the independent variable in explaining the dependent variable by 35.9%, while the rest of 64.1% is explained by other variables outside the model of this study. While the F test values obtained 11.717 > 2.19 and significant at 0.000 <0.05, the independent variables simultaneously influence on the dependent variable. From the results of hypothesis testing showed that the variable Leverage has a significant positive effect on ETR. And profitabilty has a significant negative effect on ETR. While on the Size, Inventory Intensity, Fixed Asset Intensity, and Independent Commissioner showed no effect on the ETR.Keywords: Firm Size, Leverage, Inventory Intensity, Profitability, Fixed AssetIntensity,Independent Commissioner, and Effective Tax Rate